Rhodium-Catalyzed Highly Enantioselective Addition of Arylboronic Acids to Cyclic Aldimines: Practical Asymmetric Synthesis of Cyclic Sulfamidates - Wang, Hui; Xu, Ming-Hua (Synthesis, 2013)
A highly efficient asymmetric arylation of cyclic N-sulfonyl aldimines with arylboronic acids catalyzed by a rhodium/ sulfur–olefin ligand complex under mild conditions is described. A wide range 4-aryl-3,4-dihydro-1,2,3-benzoxathiazine 2,2-dioxides were obtained in extremely high yields (93–99%) and high enantiomeric purities (97–99% ee).
Keywords: asymmetric catalysis; cyclization; arylation; rhodium; boron; ligands; sulfamidates; heterocycles